Econometric modelling of compound cyclicality of using telecommunication services - Kaczmarczyk, Paweł (Ekonometryczne modelowanie złożenia cykliczności korzystania z usług telekomunikacyjnych, 2021)
The aim of this study was to test the effectiveness of an econometric model with dichotomous (binary) explanatory variables in the approximation and prediction of different kinds of cyclicality (annual, monthly, weekly, and daily) of demand for telephone services. The analyses were conducted with the use of data provided by the selected telecommunication network operator. The data included hourly combined demand for specified telephone services (in seconds) of outgoing calls within the framework of the particular subscriber group (business or individual), the given day, the particular month, and the specific category of connection. All kinds of the cyclicality were confirmed in models with 70 explanatory variables (i.e. in models without holidays). The inclusion of the variables set denoting specific holidays improved goodness of the models fit to the data. The econometric modelling of cyclical components and the forecasting of it with the use of dichotomous variables was effective
Econometrics = Ekonometria, 2021, Vol. 25, No. 2, s. 27-45
Keywords: cyclical components; decision support system; prediction system; short-term forecasting; komponenty cyklicze; system wspomagania decyzji; system predykcyjny; prognozowanie krótkookresowe